A Displacement-Based Theory for Predicting the Support Force on the Shield Tunneling Surface in Sandy Soil Layers - Guang Sun; Han Liu; Zhiyuan Guo; Ranjie Li; Tao Li (Advances in Civil Engineering)
Due to the poor stability of the loose sandy soil layer, if the support force is not properly controlled during the construction process of the shield tunnel using the earth pressure balance method, it is easy to cause the ground to collapse or uplift. Therefore, understanding the support force of the excavation surface of shield tunneling in sandy soil layer is very vital to ensure the stability of the excavation surface. Firstly, it is assumed that the damaged soil is a three-dimensional wedge and a modified three-dimensional wedge in the active and passive failure modes, respectively. The shallow soil pressure theory and the soil plastic limit equilibrium theory are derived by analyzing the stress distribution on the damaged soil. The equation for revealing the inner essence between the support force of the shield excavation surface and excavation surface displacement under the condition of sand-covered soil is used. Secondly, the numerical simulation method analyzes the displacement of the excavation surface when the support force changes under different working conditions, and the relationship curve between the excavation surface support force and the shield tunneling displacement is obtained. The comparison and analysis between the numerical simulation calculation and the theoretical analysis indicate that the deduced calculation equation for the excavation surface support force based on the displacement earth pressure is reasonable.